The Effect of Workload on the Performance of Nurses in the Inpatient Installation of RSUP Dr. Tadjuddin Chalid Makassar - Niartiningsih, Andi; Khairunnisa, Anis; Nur, Nurul Hidayah (International Journal Papier Advance and Scientific Review, 2021)
Performance is work performance or work results in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. This study aims to analyze the effect of workload on the performance of nurses in the Inpatient Installation of Dr. RSUP. Tajuddin Chalid Makassar. This type of research is a quantitative research using an observational study with a cross sectional study design. Sampling used total sampling so that the sample in this study were nurses at the Inpatient Installation of Dr. RSUP. Tajuddin Chalid Makassar, totaling 73 respondents. The results showed that there was an effect of time load on the performance of nurses, there was an effect of physical burden on the performance of nurses. there is an effect of psychological pressure on the performance of nurses in the Inpatient Installation of Dr. RSUP. Tajuddin Chalid Makassar. Therefore, it is hoped that the hospital management will increase the knowledge and skills of nurses so that they are able to compensate for the difficult work through providing training, the need to improve nursing management by making SOPs, especially the division of tasks and working hours of nurses so that they can be adjusted to the nurse's workload